Strategi Pengembangan Usaha Nasi Kuning Golden City Dengan Menggunakan Analisis SWOT - Gunawan, Nabila Alifiyah; Yunita, Tyna (Prisani Cendekia, 2024)
Using SWOT analysis as a marketing approach, this study examines the strengths, weaknesses, opportunities, and threats faced by Nasi Kuning Mpok Yuli, which is the subject of the research. Based on descriptive analysis findings, Nasi Kuning Mpok Yuli has several internal elements relevant to the products it offers, such as a strategic location in a densely populated area and few comparable competitors. The weaknesses and threats faced by Mpok Yuli's business, such as inadequate financial recording, passive offline marketing, and a lack of reliance on digital marketing for product promotion, must be considered alongside the business's strengths and opportunities.